XVII-wieczny poradnik rolniczy. Lingwistyczna charakterystyka gatunku (na przykładzie traktatów agronomicznych Jakuba Kazimierza Haura) - Galilej, Cecylia (Papers in Linguistics, 2019)
This article is an attempt at a text type analysis of a seventeenth-century agricultural guidebook on the basis of three very popular agrarian books by Jakub Kazimierz Haur, an experienced mogul property administrator and writer. The structural and semantic components of the text pattern in the collected material is determined by extracting units of the text bigger then the sentence and exploring their relationship. This kind of a typological approach can characterize an agrarian guide (and other contemporary varieties of a guide because of their formal similarity) as a standard text organization and contribute to the development of the overall characteristics of the entire genre.